2018
DOI: 10.3349/ymj.2018.59.9.1064
|View full text |Cite
|
Sign up to set email alerts
|

S100A4Gene is Crucial for Methionine-Choline-Deficient Diet-Induced Non-Alcoholic Fatty Liver Disease in Mice

Abstract: PurposeTo explore the influence of S100 calcium binding protein A4 (S100A4) knockout (KO) on methionine-choline-deficient (MCD) diet-induced non-alcoholic fatty liver disease (NAFLD) in mice.Materials and MethodsS100A4 KO mice (n=20) and their wild-type (WT) counterparts (n=20) were randomly divided into KO/MCD, Ko/methionine-choline-sufficient (MCS), WT/MCD, and WT/MCS groups. After 8 weeks of feeding, blood lipid and liver function-related indexes were measured. HE, Oil Red O, and Masson stainings were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
3
3
0
Order By: Relevance
“…Mice fed the MCD diet had increased triglycerides in the liver [22, 46, 47] and this was also found in the present study. WT2 mice had about two-fold higher triglyceride levels than WT1 animals irrespective of the diet.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Mice fed the MCD diet had increased triglycerides in the liver [22, 46, 47] and this was also found in the present study. WT2 mice had about two-fold higher triglyceride levels than WT1 animals irrespective of the diet.…”
Section: Discussionsupporting
confidence: 89%
“…Upregulated and unchanged IL-6 mRNA expression in MCD-NASH liver were identified in the different mouse groups analyzed herein and was also reported in separate studies by others [46, 47]. Chemerin was found increased in NASH liver of MCD diet fed rodents [48] and was also higher in one of the present models.…”
Section: Discussionsupporting
confidence: 86%
“…ORO staining was performed for the determination of TG contents in liver tissues according to published literature (20). Briefly, tissue sections were fixed for 10 min with 10% ice paraformaldehyde and washed by distilled water three times after placed on slides for 30 min at room temperature.…”
Section: Oro Stainingmentioning
confidence: 99%
“…According to the earlier paper (20), liver sections were executed HE stains for measurement of hepatic histology. The tissue sections were observed and photographed with ×100 and ×200 original magnification under an electronic microscope.…”
Section: The He Stainsmentioning
confidence: 99%
“…Also, we examined the correlation between AOD S100A4 and CVF in the tissue samples, and the results revealed an excellent reliable correlation between these parameters, indicating that S100A4 may represent a positive regulatory factor promoting cancer-associated collagen deposition. Studies have reported that S100A4 plays a vital role in various nontumor diseases, such as fibrosis, inflammation, immune response, and neuroprotection, where it regulates tissue fibrosis via different signaling pathways and stimulates fibroblasts to secrete collagen, inducing collagen deposition (19)(20)(21)(22)(23)(24). These results suggest that S100A4 may regulate collagen deposition in tumor disorders via other signaling pathways; we have begun to investigate the possible signaling mechanisms using in vivo and in vitro methods.…”
Section: Discussionmentioning
confidence: 97%